Piperacillin-Associated Pulmonary Infiltrates with Eosinophilia: A Case Report - Olivia Ling-I Tseng; John Thomas Kelsall; Pearce George Wilcox (Canadian Respiratory Journal)
A case of pulmonary infiltrates with eosinophilia attributed to piperacillin/tazobactam therapy is described. A 54-year-old woman was treated for a suspected severe urinary tract infection with piperacillin/tazobactam. Four days later, she developed fever, chills, shortness of breath and intermittent chest pains. Eosinophilia was noted in peripheral blood and, subsequently, on bronchoalveolar lavage. Transbronchial biopsy showed tissue infiltrates with eosinophilia. No evidence of bacterial, fungal and parasitic infection, or vasculitis was observed. Her symptoms and peripheral eosinophilia subsided after drug discontinuation and oral prednisone treatment. Piperacillin is an extended-spectrum penicillin antibiotic prescribed for moderate to severe infections. The common adverse reactions to piperacillin include nausea, vomiting, diarrhea and rash. Pulmonary infiltrates with eosinophilia is a rare adverse reaction, but one that may result in significant morbidity. Physicians should be aware of this rare but important adverse reaction to piperacillin.